2019
DOI: 10.3390/s19040941
|View full text |Cite
|
Sign up to set email alerts
|

Zinc/Aluminium–Quinclorac Layered Nanocomposite Modified Multi-Walled Carbon Nanotube Paste Electrode for Electrochemical Determination of Bisphenol A

Abstract: This paper presents the application of zinc/aluminium-layered double hydroxide-quinclorac (Zn/Al-LDH-QC) as a modifier of multiwalled carbon nanotubes (MWCNT) paste electrode for the determination of bisphenol A (BPA). The Zn/Al-LDH-QC/MWCNT morphology was examined by a transmission electron microscope and a scanning electron microscope. Electrochemical impedance spectroscopy was utilized to investigate the electrode interfacial properties. The electrochemical responses of the modified electrode towards BPA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 49 publications
0
13
0
2
Order By: Relevance
“…Jadi, minyak bumi merupakan campuran heterogen yang tersusun atas senyawa kimia yang diolah dari minyak mentah menjadi produk yang bisa digunakan masyarakat. Penyusun minyak bumi umumnya tersusun atas carbon [38][39][40] 84-87% dan hidrogen [41][42] 11-14% dan senyawasenyawa [43] lainnya seperti sulfur [44] , nitrogen [45][46] , dan oksigen [47][48][49][50] . Untuk pemenuhan produksi minyak tersebut pengimporan BBM [51] harus di lakukan untuk pengoptimalan kilang minyak yang berada di dalam negeri [52] .…”
Section: Pendahuluanunclassified
“…Jadi, minyak bumi merupakan campuran heterogen yang tersusun atas senyawa kimia yang diolah dari minyak mentah menjadi produk yang bisa digunakan masyarakat. Penyusun minyak bumi umumnya tersusun atas carbon [38][39][40] 84-87% dan hidrogen [41][42] 11-14% dan senyawasenyawa [43] lainnya seperti sulfur [44] , nitrogen [45][46] , dan oksigen [47][48][49][50] . Untuk pemenuhan produksi minyak tersebut pengimporan BBM [51] harus di lakukan untuk pengoptimalan kilang minyak yang berada di dalam negeri [52] .…”
Section: Pendahuluanunclassified
“…Pada kali ini pembuatan asam sulfat menggunakan metode sintesis. Asam sulfat (H 2 SO 4 ) [40] disintesis dari [42] belerang (S), oksigen (O 2 ), dan air menggu [60] nakan katalis [5] , pada proses kontak digunakan katalis vanadium pentaoksida (V 2 O 5 ), dan pada proses bilik timbal NO 2 .…”
Section: Proses Preparasi Asam Sulfatunclassified
“…These polymer materials are mostly used to produce storage containers, nursing bottles, thermal papers, medical apparatus, food can linings and supply pipes [3]. However, toxicology studies have shown that BPA is a typical endocrine-disrupting compound (EDC) in which even a low level can mimic and interfere with hormonal activity by interfering with growth and reproductive development [4,5]. Consequently, the popular use of BPA has raised serious concerns regarding its implications for food safety and environmental health.…”
Section: Introductionmentioning
confidence: 99%